(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Ability listening is one skills still Lots get constraints. as We know together that talk and listen said as required activities speaker and listener. because that is, skill listening is one Skills important language learned . Ability good listening is also very influential to success study, success Study can walk with Good if student capable catch message or information about teaching material delivered by the teacher or from material watch . One way to create fun learning is that the teacher must have effective methods, strategies and learning media so that the learning process can run optimally. By using this recording media, the teacher can create pleasant learning conditions for students, one of which is by using recording media. So it is expected that the ability to listen to short stories increases.